The Effect of New Normal Enforcement On The Tourism Industry Sector : Case Study at Pramuka Island - Hadi, Cecilia Valentina Sri; Imanuel, I Gusti Bagus (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This research was conducted to determine the effect of implementing new habits on the marine tourism industry on Pramuka Island. Qualitative descriptive methods were used in this research. Primary data acquisition techniques were carried out through observation and interviews with stakeholders organizing tourism activities on Pramuka Island, Seribu Islands. Respondents were selected based on fulfilling aspects of attractions, amenities and accessibility that are important in developing a tourist location. The research results show that the implementation of new habits has had a positive impact on the sustainability of the tourism industry on Pramuka Island in the new normal era. Keywords: Covid 19 pandemic, marine tourism, new habits